Concurrency Control in Distributed Databases: A Systematic Review - Lloyd Moluma, Tshidiso; Esiefarienrhe, Bukohwo Michael (AI Society & STMIK Indonesia, 2025)
This paper provides a comprehensive review of concurrency control techniques used in distributed database systems. It focuses on recent developments by examining articles and other academic documents published between 2016 and 2025. Using PRISMA 2020 guidelines, 197 scientific and academic studies were screened across major databases, and 10 articles met the final criteria for detailed analysis. The review classifies concurrency control approaches into four areas: types of locks, performance, accuracy, and efficiency. Each classification is then evaluated based on throughput, latency, detection accuracy, scalability, and technique applied to enhance these metrics. The findings demonstrate that traditional algorithms maintain consistent performance in general conditions but often struggle under heavy contention. Contrastingly, multi-version concurrency control and optimistic techniques improve scalability but introduce high abortion rates. Emerging adaptive techniques that depend on workload profiling show increasing promises for dynamic environments. The review highlights these trends and outlines future research direction for resilient distributed systems.